Judicial Commission and Wilayat Al-Mazalim: A Comparative Study on The Independence of Judicial - Sultan Ahmad A'thoillah; M. Afiq Zamzami Mawardi; Weldani Zahira; Rina Antasari (Fakultas Syariah dan Hukum UIN Raden Fatah Palembang, 2026)
This study addresses the limitations of the Judicial Commission in Indonesia in exercising effective judicial oversight, particularly due to its restricted constitutional authority in supervising judges’ conduct and maintaining judicial integrity. The research compares the Judicial Commission within Indonesia’s constitutional framework with the institution of Wilayat al-Mazalim in the classical Islamic legal tradition to explore alternative concepts of independent judicial oversight. This study aims to analyze the relevance of Wilayat al-Mazalim in strengthening the role and authority of the Judicial Commission in contemporary judicial governance. Using a qualitative method with a normative-comparative approach, the study examines and compares the two institutions in terms of authority, institutional legitimacy, supervisory functions, and mechanisms of accountability through library research involving constitutional regulations, legal scholarship, and classical Islamic legal literature, including al-Mawardi’s Al-Ahkam al-Sultaniyyah. The findings reveal that both institutions share fundamental principles of justice, ethical supervision, and accountability in judicial conduct. However, Wilayat al-Mazalim possessed broader judicial and executive authority under the caliphal system, while the Judicial Commission functions within constitutionally restricted supervisory powers that limit its enforcement capacity. The novelty of this study lies in its integration of classical Islamic constitutional thought into contemporary discourse on judicial reform in Indonesia. The study concludes that the principles embodied in Wilayat al-Mazalim may provide a conceptual foundation for strengthening the authority and effectiveness of the Judicial Commission in promoting judicial accountability and enhancing public trust in the judiciary.